Systematic Literature Review: Hambatan dan Peluang Penerapan SAK EMKM Di Indonesia - Tiara Abdurahman; Fityan Halid; Mattoasi Mattoasi; Hartati Tuli (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) were issued to assist MSMEs in preparing simpler financial statements while remaining compliant with accounting principles. However, numerous studies indicate that the implementation of SAK EMKM remains suboptimal across regions and business sectors in Indonesia. This study aims to map the barriers and opportunities for SAK EMKM implementation using a Systematic Literature Review (SLR) approach. The findings reveal that implementation barriers originate from three main layers: internal capacity constraints, socio-structural factors, and institutional limitations. Despite these challenges, the study identifies several opportunities for strengthening implementation, including capacity-building initiatives, bookkeeping digitalization, cross-institutional collaboration, and external incentives such as financing requirements based on standardized financial reports. This study contributes a comprehensive mapping of barriers and opportunities, providing a valuable reference for policymakers, academics, and MSME facilitators in formulating more effective and sustainable SAK EMKM implementation strategies.